Morphological variability of otolith organs in three congeneric Pagellus species - Bostanci Derya; Yedier Serdar; Türker Dilek; Işmen Ali (Oceanological and Hydrobiological Studies)
Morphological features of sagittal otoliths in Pagellus acarne, P. bogaraveo, and P. erythrinus samples collected from the Aegean Sea were used to assess the variability both between Pagellus species and between otolith pairs employing scanning electron microscopy (SEM) and contour shape analysis. Twenty-one otolith morphological characters were compared in detail using SEM analysis. Twelve of these characters differ between Pagellus species and are suitable for distinguishing between the three congeneric Pagellus species. Wavelet functions of otolith contour shape were compared for six Pagellus groups. The wavelet functions obtained from the contour shape analysis showed high variability in the antero-dorsal, postero-dorsal, and antero-ventral regions of otoliths among the six groups analyzed. The results of principal component analysis (PCA) of the wavelet data provided a clear distinction between the groups under study. Cluster analysis supported the PCA results and basically divided them into two main branches. One of these branches contained only P. erythrinus, while P. acarne and P. bogaraveo were present in the other branch. This is the first study to provide detailed morphological characters and wavelet analysis of left- and right-side otoliths in these three congeneric Pagellus species from the Aegean Sea.